1991
DOI: 10.1002/ar.1092310306
|View full text |Cite
|
Sign up to set email alerts
|

Solitary neuroendocrine cells and neuroepithelial bodies in the lower airways of embryonic, fetal, and postnatal sheep

Abstract: The sheep pulmonary intraepithelial APUD system was studied by histochemical, immunocytochemical, and electron microscopy techniques during different periods of lung development: embryonic, fetal (pseudoglandular, canalicular, and alveolar), and postnatal. The cells of the ovine pulmonary intraepithelial APUD system were found randomly distributed throughout the conducting and respiratory or undifferentiated airways. They appeared as isolated cells (solitary neuroendocrine cells) or in groups (neuroepithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…by light microscopic immunohistochemistry [5][6][7]. To the best of our knowledge, so far only a few studies have analyzed the intraepithelial endocrine cells during the different developmental stages of lung in the fetal sheep lower respiratory tract [8]. However, the agerelated changes of pulmonary endocrine cells of sheep from fetal period to adult are still not well known.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…by light microscopic immunohistochemistry [5][6][7]. To the best of our knowledge, so far only a few studies have analyzed the intraepithelial endocrine cells during the different developmental stages of lung in the fetal sheep lower respiratory tract [8]. However, the agerelated changes of pulmonary endocrine cells of sheep from fetal period to adult are still not well known.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our present study is the first to document precisely the developmental course of pulmonary endocrine cells in sheep lungs by the immunohistochemical quantitative analysis. Recent immunohistochemical studies of various kind of mammals showed that the pulmonary endocrine cells have various kinds of neuroendocrine markers such as serotonin [1,9,11,12,18,21,28], bombesin [1,6,12,23,24,28], gastrin-releasing peptide [1], cholecystokinin [27], calcitonin [1,12,23], calcitonin gene related peptide [1,28], leuenkephalin [1,12], NSE [1,8,18] and chromogranin [1].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations